Effects of Shenlian extract on experimental atherosclerosis in ApoE-deficient mice based on ultrasound biomicroscopy. Issue 1 (December 2016) - Guo, Yan; Liu, Xu-Cen; Wang, Ya-Jie; Li, Qi; Yang, Qing; Weng, Xiao-Gang; Chen, Ying; Cai, Wei-Yan; Kan, Xiao-Xi; Chen, Xi; Huang, He-Fei; Zhu, Xiao-Xin; et al.
Abstract Background This study directly and dynamically investigated the effects of SL extract (i.e., a combination ofRadix Salviae miltiorrhizae andAndrographis paniculata extract) on plaque progression in vivo by high resolution ultrasound biomicroscopy (UBM). Methods An atherosclerosis model was established by placing a perivascular collar on the right common carotid artery in apolipoprotein E-deficient (ApoE-/- ) mice. Thickness, plaque area and local blood flow were observed by UBM, pathological changes were observed by histochemical staining, and lipid levels were measured by respective commercially available kits. Results Compared with the model group, the SL extract groups showed reduced wall thickness of the aortic arch (GC:P = 0.001, P = 0.002, andP < 0.001; LC:P < 0.001, P < 0.001, andP < 0.001; BC:P = 0.027, P = 0.017, andP = 0.003; respectively), which presented with retarded plaque progression of the cartoid artery with concordantly increased blood flow (P = 0.002 andP < 0.001) as visualized in vivo by UBM. Histological analysis confirmed the reduction of carotid atherosclerosis. Conclusions The SL extract inhibited the formation of atherosclerotic plaques in an ApoE-/- mice model by UBM analysis, and did so by effects that ameliorated local blood flow and improved blood lipid levels.